Chlorination of Benzylic and Allylic Alcohols with Trimethylsilyl Chloride Enhanced by Natural Sodium Montmorillonite - Tandiary, Michael Andreas; Masui, Yoichi; Onaka, Makoto (Synlett, 2014)
A new and practical method for the efficient chlorination of tertiary, secondary, and primary benzylic and allylic alcohols is described. The method is characterized by the formation of hydrogen chloride from trimethylsilyl chloride and trace water, the formation of a carbenium ion through the protonation of an alcohol and subsequent dehydration, and the chlorination of the carbenium ion. During the process, sodium ion-exchanged montmorillonite plays a crucial role in capturing the generated hydrogen chloride, stabilizing the carbenium intermediate as well as promoting the chlorination.
Keywords: hydrous sodium montmorillonite; chlorination; benzylic alcohols; allylic alcohols; trimethylsilyl chloride